SEDIMENT CHARACTERISTICS TO SUPPORT THE REVITALIZATION OF TPPI TUBAN PORT, EAST JAVA, INDONESIA - Rachman, Reno Arief; Wibowo, Mardi; Widagdo, Aloysius Bagyo; Rahili, Nurkhalis; Yuniardi, Rizaldi Caesar; Suharyanto, Hamzah Haru Radityo; Hamid, Affandy; Subarkah, Aris; Suranto, Suranto; Khoirunnisa, Hanah (BULLETIN OF THE MARINE GEOLOGY, 2024)
TPPI Tuban Port is located in Tuban Regency, East Java. Geologically, the rocks are composed of reef limestone in the Paciran Formation, which is Pliocene–Early Pleistocene. The importance of complying with jetty capacity standards and water conditions in commercial ports is emphasized as the key to maintaining smooth port operations, making port revitalization a necessity. One of the main aspects to consider is the sedimentation problem, closely related to sediment characteristics. A deep understanding of sediment dynamics is essential for designing effective solutions to ensure the sustainability of port operations. This research aims to determine the distribution pattern of bed load characteristics such as water content, specific gravity, gradation, sediment texture, d50 size of sediment grains, and statistical analysis of bed load sediment in the west and rainy seasons, where the influence of sediment from land is very large. so it is hoped that it can support the port revitalization plan. The methods used include taking sediment samples in the field, testing sediment samples in the laboratory, statistical sediment analysis, and descriptive analysis of bed load characteristics using the Gradistat method. Based on the study results, the water content value ranges from 22.446% to 218.289%, and the specific gravity ranges from 2,100 g/m³ to 2.690 g/cm³. Additionally, the grain size varies from 0.080 mm to 0.900 mm, and the average grain size ranges from 261.1 μm to 2657.5 μm. Sediment sorting is dominated by very poorly sorted materials, with statistical analysis indicating a dominance of the very platykurtic type. The lithological type is predominantly sand.